2016
DOI: 10.1177/0042098016634578
|View full text |Cite
|
Sign up to set email alerts
|

Do neighbourhood facilities matter for slum housing? Evidence from Indian slum clusters

Abstract: Slum dwellers in developing countries reside in inhuman conditions, with little provision of basic facilities and with considerable overlap between sources of drinking water supply, sewerage and the area for garbage disposal. Is it because clean environment does not enter their decision function for residence selection or is it simply non-affordability? We examine these questions in the context of the registered slum clusters of four Indian cities – Mathura, Ujjain, Jaipur and Ludhiana. A primary survey was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
0
8
0
2
Order By: Relevance
“…On the contrary, it is evidenced that the building age negatively affects the price of properties (Chen & Jim, 2010). Urban amenities are also quite influential on the housing prices; the study conducted by Das et al (2017) revealed that neighborhood amenities positively impact the price of residential housings even in the slum clusters. Residents showed more willingness to pay for the location with facilities like sewerage and street lights.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the contrary, it is evidenced that the building age negatively affects the price of properties (Chen & Jim, 2010). Urban amenities are also quite influential on the housing prices; the study conducted by Das et al (2017) revealed that neighborhood amenities positively impact the price of residential housings even in the slum clusters. Residents showed more willingness to pay for the location with facilities like sewerage and street lights.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to insufficient access to clean water, trenches and water channels are inevitably used for waste disposal. Even though such conditions are inhumane for slum dwellers (Das et al, 2017), their low incomes force them to remain in such areas in order to meet their housing needs (Vasudevan, 2015). Supriatna & van der Molen (2014) confirm that slums are urban residential villages consisting of dense and spontaneously growing environments in the centres or outskirts of cities.…”
Section: Introductionmentioning
confidence: 95%
“…They conducted a survey in slums in India, and employed a hedonic approach. They found that house prices vary according to various structural variables, and the government provides only two of the neighborhood features -streetlight and sewage facility 18) . While there are some studies that reveal slum dwellers' housing preferences, the number is limited; more studies are required in various places and for various household attributes.…”
Section: Literature Review On Low-income Group Housing Issues In Urbamentioning
confidence: 99%